2015
DOI: 10.1080/17451000.2015.1044998
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and distribution of the swimming crabCallinectes danaeSmith, 1869 (Crustacea, Decapoda, Portunidae) in the Ubatuba region, southeastern Brazil

Abstract: This study analysed the spatio-temporal distribution of Callinectes danae considering some environmental factors in three bays in Ubatuba, São Paulo, Brazil: Ubatumirim, Ubatuba and Mar Virado. Sampling was performed monthly (from January 1998 to December 1999) using a shrimp fishery boat provided with double rig nets. Six transects were established in each bay, three being in areas protected from wave action (at 5, 7.5 and 10 m depth) and three in exposed areas (at 10, 15 and 20 m). A total of 3039 specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
3
3
0
Order By: Relevance
“…To conclude, this study showed that, as reported for C. ornatus (Andrade et al, 2014) and C. danae (Barreto et al, 2006 andAntunes et al, 2015), juveniles and adults of A. spinimanus were distributed differently between depths and months, corroborating our hypothesis. Juveniles were widely distributed, from shallower areas 5 m deep to areas 35 m deep, and were more abundant in summer, whereas adults were more abundant at greater depths (20−25 m), in winter and spring.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…To conclude, this study showed that, as reported for C. ornatus (Andrade et al, 2014) and C. danae (Barreto et al, 2006 andAntunes et al, 2015), juveniles and adults of A. spinimanus were distributed differently between depths and months, corroborating our hypothesis. Juveniles were widely distributed, from shallower areas 5 m deep to areas 35 m deep, and were more abundant in summer, whereas adults were more abundant at greater depths (20−25 m), in winter and spring.…”
Section: Discussionsupporting
confidence: 90%
“…According to Hines et al (1987), the high number of juveniles at shallower depths may be related to the greater availability of shelter and food. A higher abundance of juveniles at lower depths was also observed by Santos et al (1995) with A. spinimanus, Heck et al (2001 with Callinectes sapidus Rathbun 1896, Andrade et al (2014) with C. ornatus and Antunes et al (2015) with C. danae.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…For instance, Santos, Negreiros-Fransozo & Fransozo (1994) and Pinheiro, Fransozo & Negreiros-Fransozo (1996) observed that the distributions of A. spinimanus and Arenaeus cribarius (Lamarck, 1818), respectively, were associated with sediment texture. Pinheiro, Fransozo & Negreiros-Fransozo (1997) ; Santos (2000) , Chacur & Negreiros-Fransozo (2001) , Andrade et al (2013) ; Andrade et al (2014) , Lima et al (2014) , Martins et al (2014) , and Antunes et al (2015) related the distribution of Portunoidea with bottom temperature.…”
Section: Introductionmentioning
confidence: 98%